Dynamic Calcium Release From Endoplasmic Reticulum Mediated by Ryanodine Receptor 3 Is Crucial for Oligodendroglial Differentiation - Li, Tao; Wang, Lingyun; Ma, Teng; Wang, Shouyu; Niu, Jianqin; Li, Hongli; Xiao, Lan (Frontiers in Molecular Neuroscience, 2018)
Increased intracellular Ca2+ in oligodendrocyte progenitor cells (OPCs) is important to initiate their differentiation, but the intracellular Ca2+ channel involved in this process remains unclear. As a Ca2+-induced Ca2+ release channel that mediates endoplasmic reticulum (ER) Ca2+ release, the role of ryanodine receptors (RyRs) in oligodendroglial development is unexplored. In the present study, we observed that among the three mammalian isoforms, oligodendroglial lineage cells selectively expressed RyR3. Strong RyR3-positive signal was distributed all over the cytoplasm and processes in OPCs and/or immature OLs (imOLs), whereas it gradually decreased and was located mainly around the perinuclear region in mature oligodendrocytes (OLs). In addition, RyR3-mediated intracellular Ca2+ waves following caffeine stimulation were correlated with the expression pattern of RyR3, in which high flat Ca2+ fluctuations and oscillatory Ca2+ waves were more frequently recorded in OPCs and/or imOLs than in OLs. Through further functional exploration, we demonstrated that pretreatment with the RyR antagonist ryanodine could neutralize the increase in intracellular Ca2+ induced by OPC differentiation and reduce the number of mature OLs. Moreover, gene-level knockdown of RyR3 by lentivirus in OPCs resulted in inhibition of OPC differentiation. Taken together, our results provide new insight into the crucial role of RyR3-mediated ER Ca2+ release in the regulation of OPC differentiation and/or myelination.